Metabolic engineering of cucurbitacins in Cucurbita pepo hairy roots - Almeida, Aldo; Dong, Lemeng; Thorsen, Theis H.; Raadam, Morten H.; Khakimov, Bekzod; Carreno-Quintero, Natalia; Kampranis, Sotirios C.; Bak, Søren (Frontiers in Plant Science, 2022)
In this paper we show that metabolic engineering in Cucurbita pepo hairy roots can be used to both effectively increase and modify cucurbitacins. Cucurbitacins are highly-oxygenated triterpenoids originally described in the Cucurbitaceae family, but have since been found in 15 taxonomically distant plant families. Cucurbitacin B, D, E and I are the most widespread amongst the Cucurbitaceae and they have both important biological and pharmacological activities. In this study C. pepo hairy roots were used as a platform to boost production and alter the structures of the afore mentioned cucurbitacins by metabolic engineering to potentially provide new or more desirable bioactivities. We report that the ability to induce cucurbitacin biosynthesis by basic Helix-Loop-Helix transcription factors is partially conserved within the Cucurbitaceae and therefore can potentially be used as a biotechnological tool to increase cucurbitacins in several genera of this family. Additionally, overexpression of a novel acyltransferase from cucurbitacin producing Iberis amara generates a hitherto undescribed acetylation at the C3-hydroxyl group of the cucurbitadienol backbone. While overexpression of the cytochromes P450 CsCYP88L2 and McCYP88L7 from Cucumis sativus and Momordica charantia (respectively), results in accumulation of new spectral feature as revealed by High resolution liquid chromatography mass spectroscopy analysis; the m/z of the new peak supports it might be a cucurbitacin hydroxylated at the C19 position in C. pepo hairy roots. Finally, this paper is a case study of how hairy roots can be used to metabolically engineer and introduce novel modifications in metabolic pathways that have not been fully elucidated.